Casein Kinase II exacerbates rheumatoid arthritis via promoting Th1 and Th17 cell inflammatory responses. (2nd November 2021) - Ye, Hua; Fu, Dongdong; Fang, Xiangyu; Xie, Yang; Zheng, Xi; Fan, Wenqiang; Hu, Fanlei; Li, Zhanguo
ABSTRACT: Objectives: Studies have demonstrated that CK2 is engaged in CD4 + T cell proliferation and activation. We investigated the potential involvement of CK2 in the pathogenesis of rheumatoid arthritis (RA). Methods: Peripheral blood and synovial fluid mononuclear cells (PBMC and SFMC) of RA patients, as well as splenocytes of collagen-induced arthritis (CIA) mice were treated with different doses of CK2 inhibitor CX4945 in vitro . Then, the Th1, Th2, Th17, and Treg cell responses were analyzed. In addition, CIA mice were administrated with CX4945 via oral gavage. Accordingly, the arthritis scores, bone destruction, tissue damage, and the CD4 + T cell subsets were assessed. Results: The expression of CK2 was upregulated in CD4 + T cells under RA circumstance. In vitro CX4945 treatment significantly inhibited the Th1 and Th17 cell responses, while promoted the Th2 cell responses in RA patient PBMC, SFMC and CIA mouse splenocytes, dampening IFN-γ and IL-17A production. Moreover, administration of CX4945 ameliorated the severity of arthritis in CIA mice, along with decreased Th1 and Th17 cells. However, CX4945 seemed to have minimal effect on RA Treg cells. Conclusion: CK2 serves as an important regulator of the Th1 and Th17 cell axes in RA, thus contributing to the disease aggravation.